Optimization of family functions and parental support in improving student's academic adjustment ability - Fitriani Yustikasari Lubis; Shafia Islaha; Witriani Witriani; Puspita Adhi Kusuma Wijayanti; Kayisa Zariayufa; Dinda Oktavia Pradina (University of Merdeka Malang, 2023)
Changes in learning patterns both before and after the COVID-19 Pandemic require students to have adjustment abilities. The ability of students to adjust academically in blended learning does require not only teachers' support at school but also the role of parents at home. Well-functioning family is also an important supporting environment for students to have an excellent academic adjustment. To assist parents in helping and guiding students in academics, a workshop for parents was carried out to optimize family functions and parental support in improving students' academic adjustment. A total of 15 parents of Junior High School 4 Jatinangor students participated in this activity. Participants were representatives' parents from grades 7 to 9 of junior high school. The results indicate an increase in parental understanding regarding the role of family functions and parental support for students' academic adjustment. Parents also responded well and were satisfied with the materials and activities.